ECG Phenomena: Pseudopreexcitation and Repolarization Disturbances Resembling ST‐Elevation Myocardial Infarction Caused by an Intraatrial Rhabdomyoma in a Newborn. (13th May 2013) - Paech, Christian; Gebauer, Roman Antonin
Abstract As is known from other reports, a rhabdomyoma or tumor metastasis may alter intracardiac electrical conduction, producing electrical phenomena like pseudopreexcitation or repolarization disturbances resembling ST‐elevation myocardial infarction or Brugada's syndrome. We present a newborn with a giant atrial rhabdomyoma and additionally multiple ventricular rhabdomyomas. He presented with several electrocardiogram (ECG) phenomena due to tumor‐caused atrial depolarization and repolarization disturbances. Except from the cardiac tumors, the physical status was within normal range. Initial ECG showed a rapid atrial tachycardia with a ventricular rate of 230 bpm, which was terminated by electrical cardioversion. Afterwards, the ECG showed atrial rhythm with frequent atrial premature contractions and deformation of the PR interval with large, broad P waves and loss of discret PR segment, imposing as pseudopreexcitation. The following QRS complex was normal, with seemingly abnormal ventricular repolarization resembeling ST‐elevation myocardial infarction. The atrial tumor was resected with consequent vast atrial reconstruction using patch plastic. The ventricular tumors were left without manipulation. After surgery, pseudopreexcitation and repolarization abnormalities vanished entirely and an alternans between sinus rhythm and ectopic atrial rhythm was present. These phenomena were supposably caused by isolated atrial depolarization disturbances due to tumor‐caused heterogenous endocardial activation. The seemingly abnormal ventricular repolarization is probably due to repolarization of the atrial mass, superimposed on the ventricular repolarization. Recognizably, the QRS complex before and after surgical resection of the rhabdomyoma is identical, underlining the atrial origin of the repolarization abnormalities before surgery.